1982
DOI: 10.1097/00003086-198209000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the Distal Humeral Chondroepiphysis in the Neonate

Abstract: Fracture of the distal humeral chondroepiphysis in the neonate is an unusual injury easily mistaken for a posterior dislocation of the elbow. Physical examination reveals the nature of the injury. Nonoperative management results in a satisfactory outcome, as demonstrated in the following illustrative case. CASE REPORTA 36-hour-old infant was noted at delivery to have a deformity of the right elbow. A difficult forcep delivery was required to assist a doublefootling breech presentation. The elbow was noted to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Dias and Menon reported similar injuries and found that the forearm extension was restricted by 12°and 10°, respectively, after closed reduction (6, 7). Downs presented a case in which the elbow extension was restricted by 12°at six months post-surgery but there were no obvious limitations in elbow bending or function (8). Barret et al presented a case in which the elbow extension was restricted by 20°at 24 months after closed reduction and external splintage (4).…”
Section: Discussionmentioning
confidence: 99%
“…Dias and Menon reported similar injuries and found that the forearm extension was restricted by 12°and 10°, respectively, after closed reduction (6, 7). Downs presented a case in which the elbow extension was restricted by 12°at six months post-surgery but there were no obvious limitations in elbow bending or function (8). Barret et al presented a case in which the elbow extension was restricted by 20°at 24 months after closed reduction and external splintage (4).…”
Section: Discussionmentioning
confidence: 99%
“…The condition is very rare. Downs and Wirth cited 11 cases of fracture separation of distal chondroepiphysis in the newborn [2]. To date in our search we have found two additional cases [1,4].…”
Section: The Injury Is Rare and Maybe Unknown To The Treating Physicianmentioning
confidence: 95%
“…Capitulum and trohlea are still unossified at this age [1,2,4]. To differentiate from posterior elbow luxation Ruo describes that medial displacement of forearm is common in PSDH while lateral displacement is usual in elbow dislocations [5].…”
Section: The Radiologic Examination Is Inconclusive For a Definitive mentioning
confidence: 99%
“…The characteristic postero-medial displacement of the distal humerus epiphysis associated with this kind of lesion was first emphasized by Valdiserri and Kelescian [2 -6], and is still confirmative if seen in any elbow X-ray, arthrogram or ultrasound scan [3, 4, 6 -8]. According to some authors, this type of fracture separation in young infants is still described as an uncommon variant of the well-known pediatric supracondylar humerus fracture [3,4,9]. Sound knowledge of the sequence of appearance of the elbow ossification centers is essential for correct diagnosis, since at birth none of the four distal humerus epiphysis ossification centers found at the termination of growth are visible.…”
mentioning
confidence: 95%
“…In the majority of cases, they do not progress until skeletal maturity. However, they are mainly, but not exclusively, reported for the infant age [4,6,11,23], while in comparable cases newborns showed a complete recovery within 3 weeks to 3 months [4,8,18,20]. Of course, traditional plane X-rays have been positive at some time in almost all cases, maybe even essential for the diagnostic work-up, since they are still considered to be superior for estimating angles and deformities [3 -5, 7, 8, 11, 19, 20, 23].…”
mentioning
confidence: 99%